2018
DOI: 10.1111/famp.12340
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Mental Health and Burden among Primary Caregivers of Outpatients with Schizophrenia

Abstract: There is growing recognition that caring for a patient with schizophrenia often results in high levels of perceived burden and poorer overall mental health for caregivers. A quantitative cross-sectional design and standardized instruments were used to collect data from 355 primary caregivers of adults in outpatient care with schizophrenia in China. Structural equation modeling was used to examine the association between caregiver burden and mental health among primary caregivers and whether this association is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
(64 reference statements)
0
22
1
1
Order By: Relevance
“…For instance, the World Health Organization World Mental Health Surveys [6] have shown higher caregiver burden for spouses than parents across high-and upper-middle-income countries, yet higher caregiver burden for parents than spouses from lower-or middleincome countries [29]. One study on Chinese caregivers of PLS found that parent caregivers reported higher burden than spouse caregivers [30], while another study of African caregivers of PLS showed no significant difference in caregiver burden between spouse and parent caregivers [31]. These results indicate that caregiver burden may be culture-dependent and vary by country.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the World Health Organization World Mental Health Surveys [6] have shown higher caregiver burden for spouses than parents across high-and upper-middle-income countries, yet higher caregiver burden for parents than spouses from lower-or middleincome countries [29]. One study on Chinese caregivers of PLS found that parent caregivers reported higher burden than spouse caregivers [30], while another study of African caregivers of PLS showed no significant difference in caregiver burden between spouse and parent caregivers [31]. These results indicate that caregiver burden may be culture-dependent and vary by country.…”
Section: Introductionmentioning
confidence: 99%
“…The female caregivers were seen to be significantly vulnerable of presenting higher burden in all of its form as compared to male caregivers. In summary this study found that the anxiety was higher in caregivers of male patients than caregivers of female patients (52.7% vs 38.1%, P=0.012); female caregivers were more likely to suffer from depression (51.2% vs 38.6%, P = 0.031) and anxiety (51.6% vs 38.1%, P=0.020) than male caregivers [21].…”
Section: High Burden and Burnout Of Care And Influencing Factorsmentioning
confidence: 59%
“…The assessment of burden as associated with other factors such as personality the coping style and family functioning was conducted by Yu, et al [21]. In this this study the high level of burden was directly associated with personality traits especially neuroticism personality traits and the coping style ( diathesis), and the family functioning was also found to be influencing factor of high burden and burnout [21].…”
Section: High Burden and Burnout Of Care And Influencing Factorsmentioning
confidence: 85%
See 1 more Smart Citation
“…The study results are similar to the literature. 33 Negative self-perception score is lower in the caregivers whose patient hospitalized first-time (Table 3). In conclusion, it is suggested that the caregiver of the patients who are hospitalized for the first time had spent less time in care as compared with the other patient relatives.…”
Section: Resultsmentioning
confidence: 98%